The Bible and Homosexuality in Zimbabwe. A Socio-historical analysis of the political, cultural and Christian arguments in the homosexual public debate with special reference to the use of the Bible - Gunda, Masiiwa Ragies (Bible in Africa studies, 2010)
BiAS 3 is a monograph which was submitted and passed as PhD thesis at the University of Bayreuth, Germany. The author revisits the subject of homosexuality in Zimbabwe, a subject that attracted the attention of the international community from 1995 when Robert Gabriel Mugabe, the President of Zimbabwe described homosexual persons as “worse than dogs and pigs”. The President’s position was widely supported by Christians and Traditionalists alike, and the Bible was used as the final arbiter, as it is the “Word of God”. The Bible was also used by homosexual persons and those sympathetic to them, such that the Bible fought against the Bible. The book highlights the interconnection between homosexuality, religion and the socio-economic and political challenges from the 1990s, and raises critical questions about the widespread selective-literal appropriation of the Bible, a practice that ignores the socio-historical context of the Bible. This is a book for biblical students, scholars and ordinary readers of the Bible who want to engage with contemporary socio-theological challenges.